دور مكاتب جبهة التحرير الوطني في حشد الدعم للقضية الجزائرية في بلدان غرب أوربا 1955 - 19 - بوضربة عمر (My University, 2018)
الملخص يتناول مقالنا جانبا من النشاط الدبلوماسي لجبهة التحرير الوطني في بلدان غرب أوربا؛ والتي أبدت تضامنها وتعاونها الكاملين مع فرنسا الاستعمارية في حربها ضد الجزائريين، لكن ذلك لم يمنع دبلوماسية الثورة الجزائرية من أن تحاول اختراق أسوار هذه القلعة وتنور الرأي العام في بلدانها بحقائق الصراع الفرنسي الجزائري وأن تكشف ممارسات وتجاوزات الفرنسيين في الجزائر، انطلاقا من هذه المعطيات ارتأت ج.ت.و فتح مكاتب لها في السفارات العربية) التونسية والمغربية والمصرية( خلال سنة 1957 ، لكن اعترضت هذا المسعى صعوبات وعراقيل فتحركت الدبلوماسية الفرنسية لوقف زحف الثورة الجزائرية في أوربا الغربية. Our article addresses part of the diplomatic activity of the FLN in the countries of Western Europe , which showed solidarity and full training by colonial France in its war against the Algerians. But, this did not prevent the Algerian Revolution diplomacy from trying to penetrate the walls of this castle and enlighten the public opinion in their countries. In this context, FLN decided to open offices in the Arab embassies (Tunisian, Moroccan and Egyptian) in 1957. However, this endeavor was blocked by difficulties and obstacles. Unfortunately, this effort was hampered by the difficulties and obstacles of French diplomacy to stop the march of the Algerian revolution in Western Europe.